VARIABILITY OF CARAPACE WIDTH SIZE AND ABUNDANCE OF BLUE SWIMMING CRABS (Portunus pelagicus Linnaeus) IN PATI WATERS - Dyah Ika Nugraheni; Achmad Fahrudin; . Yonvitner (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Fishing effort enhancement would put pressure on blue swimming crab resources and its ecosystem. The objective of this study was to determine the spatial distribution based on the size of the carapace width (CW), abundance, temperature, salinity, depth, and fishing intensity in Pati waters which was divided into two zones (zones 1=nearshore, zone 2=offshore). The result showed that the average of carapace width in zone 1 to zone 2 was significantly different (p <0.05), as well as between males and females. Average number of individual (abundance) was significantly different according to fishing areas and sex (p <0.05). The average of water temperature in zone 1 was higher than in zone 2, salinity in zone 1 was smaller than in zone 2, and the water depth in zone 1 was shallower than in zone 2. The higher the crab catch intensity leaded to the smaller the abundance and size of carapace width. Alternative management strategies were proposed such as to divert fishing grounds from coastal waters to offshore during low productivity season, to uphold rules on minimum legal size for catching (Lm = 107 mm), to release of berried females catch, and to reduce accretion rate of gear and fishing fleet mainly in the coastal zone waters.Keywords: blue swimming crab, carapace widht (CW), abundance, intensity of fishing